Effect of topical ramucirumab in experimental corneal neovascularization model - Bulbul, Mustafa; Catak, Onur; Erdag, Murat; Kuloglu, Tuncay; Hancer, Serhat (Springer, 2025)
PurposeThis study aimed to compare the efficacy of topical Bevacizumab and Ramucirumab in an experimental corneal neovascularization model and to find the most effective Ramucirumab dose. Materials and methodsIn the experiments, 42 Sprague Dawley rats were randomly divided into six groups (n = 7). Corneal cauterization was applied to all groups except Group 1. Group 1 did not receive any treatment. The sham group (group 2) was applied topical dimethylsulfoxide twice daily. Group 3 was administered topical bevacizumab drops (5 mg/ml) twice daily. Groups 4, 5 and 6 received topical ramucirumab drops at a dose of 2.5, 5 and 10 mg/ml twice daily, respectively. On the 14th day, corneal photographs of all rats were taken under general anesthesia and the percentage of corneal neovascular area was calculated. VEGF, VEGFR-2 and TRPM2 immune reactivity in corneas taken after decapitation was evaluated by immunohistochemical scoring method. TAS and TOS levels were measured in blood taken from rats, and apoptosis was evaluated using the TUNEL staining method. ResultsThe percentage of corneal neovascularization areas to the entire cornea was lower in groups 3, 4, 5 and 6 compared to the sham group. VEGF, VEGFR-2 and TRPM2 immunoreactivity was observed to be statistically significantly increased in the sham group compared to the control group (p < 0.05), It was observed that there was a statistically significant decrease in groups 3, 4, 5 and 6 compared with the sham group (p < 0.05), no statistically significant difference was observed between groups 3, 4, 5 and 6 (p > 0.05). ConclusionRamucirumab can be used as a new agent in the treatment of CNV by reducing the levels of VEGF and VEGFR-2, which are CNV markers. In addition, since TRPM2 was affected statistically significantly, we think that it may be a new proangiogenic factor in CNV.
Keywords: Corneal neovascularization; Ramucirumab; Bevacizumab; TRPM2